THE MAIN INDICATORS OF EDUCATIONAL ACTIVITY DEVELOPMENTIN LAW INSTITUTE OF THE NORTH CAUCASUS FEDERAL UNIVERSITY - L. E. Botasheva; T. V. Vorotilina; A. S. Gondarenko (Гуманитарные и юридические исследования)
The article shares the experience of implementing educational programs based the Development Program of the Law Institute of the North Caucasus Federal University, independently established educational standards of the North Caucasus Federal University and the curricula . The experience contributes to the development of competitive advantages of the university at the federal level. At present, a significant number of legal experts in the government and local government, judicial and law enforcement agencies, as well as organizations in the real sector of the economy of the North Caucasus Federal District, are the graduates of the law institute of the North Caucasus federal university. Competitiveness of graduates of the Institute on the labor market of the region, their profes sional and career growth contributes to the competitiveness of the university in the market of educational services and, ultimately, its economic well-being. The article points out that in the preparation of new educational programs the institute takes into account the changing demands of employers and the changes taking place in the labor market of the region. The article summarizes the conclusions and proposals on improving educational technologies and legal training tools based on the experience of implementing modern educational programs and technologies implemented in the North Caucasus federal university. The article is of scientiic and applied nature and is aimed at solving important problems of the development of modern legal education.